2017
DOI: 10.1007/s11356-017-8754-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sperm quality in palaemonid prawns using Comet assay: methodological optimization

Abstract: The aim of this study was to adapt the Comet assay in spermatozoa of the marine prawn Palaemon serratus to use it as a marker of sperm quality. Indeed, due to the characteristics of their spermatozoa, the measurement of DNA integrity is one of the few markers which can be transferred to crustaceans to assess the quality of their semen. In the first step, the methods of collecting and maintaining spermatozoa were optimized. Cell survival was estimated during kinetics of preservation (i.e. 1, 2, 4 and 8 h) in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…Duneau et al () exposed individual males of D. magna to nicotine, followed by gentle homogenization, and obtained microscopy counts (5 × 10 4 to 1.5 × 10 6 sperm per male) consistent with the results presented here. In the marine prawn Palaemon serratus , homogenization by grinding did not decrease sperm viability when compared to other extraction techniques such as pipetting up and down, vortexing, or manual shaking (Erraud et al, ). This is consistent with the results obtained here and suggests that sperm kept their integrity during the isolation process.…”
Section: Discussionmentioning
confidence: 84%
“…Duneau et al () exposed individual males of D. magna to nicotine, followed by gentle homogenization, and obtained microscopy counts (5 × 10 4 to 1.5 × 10 6 sperm per male) consistent with the results presented here. In the marine prawn Palaemon serratus , homogenization by grinding did not decrease sperm viability when compared to other extraction techniques such as pipetting up and down, vortexing, or manual shaking (Erraud et al, ). This is consistent with the results obtained here and suggests that sperm kept their integrity during the isolation process.…”
Section: Discussionmentioning
confidence: 84%
“…Crustacean spermatozoa can also serve as a good model in ecotoxicology and biomonitoring. Spermatozoa of several amphipod crustaceans, such as Gammarus fossarum [109][110][111][112], Gammarus elvirae [113] and Echinogammarus veneri [113], as well as prawns and shrimps (Macrobrachium rosenbergii, Palaemon serratus and Palaemon longirostris) [114][115][116][117][118] were used in order to optimize the protocol or to test different toxicants as well as abiotic factors in laboratory conditions or in the field. Results also showed that spermatozoa appeared significantly more susceptible than oocytes to genotoxicants.…”
Section: Studies Performed On Invertebratesmentioning
confidence: 99%
“…157 Erraud et al ( 2018) utilised the comet assay to determine declines in sperm quality among palaemonid prawns exposed to contamination; subsequently recommending its use as a potential predictive marker for in situ biomonitoring surveys. 142 While the comet assay relies on fluorescent microscopy and only works for fresh samples, TUNEL assay can utilise either fluorescent microscopy or flow cytometry on fresh, fixed or cryopreserved samples. 134 TUNEL is a direct assay that targets DNA strand breaks by incorporating fluorescein isothiocyanate (FITC) conjugated 2′-deoxyuridine 5′-triphosphates (dUTPs) to the 3'hydroxyl (OH) breaks of single-stranded and double-stranded DNA.…”
Section: Sperm Dna Fragmentationmentioning
confidence: 99%